Medium-Throughput Detection of Hsp90/Cdc37 Protein-Protein Interaction Inhibitors Using a Split Renilla Luciferase-Based Assay - Farid Ahmad Siddiqui; Hanna Parkkola; Ganesh babu Manoharan; Daniel Abankwa (SAGE PUBLICATIONS INC, 2022)
The protein-folding chaperone Hsp90 enables the maturation and stability of various oncogenic signaling proteins and is thus pursued as a cancer drug target. Folding in particular of protein kinases is assisted by the co-chaperone Cdc37. Several inhibitors against the Hsp90 ATP-binding site have been developed. However, they displayed significant toxicity in clinical trials. By contrast, the natural product conglobatin A has an exceptionally low toxicity in mice. It targets the protein-protein interface (PPI) of Hsp90 and Cdc37, suggesting that interface inhibitors have an interesting drug development potential. In order to identify inhibitors of the Hsp90/Cdc37 PPI, we have established a mammalian cell lysate-based, medium-throughput amenable split Renilla luciferase assay. This assay employs N-terminal and C-terminal fragments of Renilla luciferase fused to full-length human Hsp90 and Cdc37, respectively. We expect that our assay will allow for the identification of novel Hsp90/Cdc37 interaction inhibitors. Such tool compounds will help to evaluate whether the toxicity profile of Hsp90/Cdc37 PPI inhibitors is in general more favorable than that of ATP-competitive Hsp90 inhibitors. Further development of such tool compounds may lead to new classes of Hsp90 inhibitors with applications in cancer and other diseases.